Vibroacoustic treatment to improve functioning and ability to work: a multidisciplinary approach to chronic pain rehabilitation - Campbell, Elsa A.; Hynynen, Jouko; Burger, Birgitta; Vainionpää, Aki; Ala-Ruona, Esa (Disability and rehabilitation, 2021)
To study the use of Vibroacoustic treatment and an added self-care intervention for improving the functioning and ability to work of patients with chronic pain and potential comorbid depressive and anxious symptoms. A mixed methods study with four single cases. Participants received bi-weekly Vibroacoustic practitioner-led treatment sessions for five weeks, followed by a one-month washout period without treatments. Then, participants conducted four self-care vibroacoustic sessions per week for five weeks, followed by another month-long washout period. Participants kept diaries of their experiences during this time. Quantitative scales included the World Health Organization Disability Assessment Schedule 2.0, Visual Analogue Scales (pain, mood, relaxation, anxiety, and ability to work), Beck's Depression Inventory-II, and Hospital Anxiety and Depression Scale (Anxiety only). The use of physiological markers was also explored. The greatest improvement was from the practitioner-led sessions, but self-care was beneficial for pain relief and relaxation. Participants became more aware of sensations in their own bodies, and during washout periods noticed more clearly the treatment effects when symptoms returned. An added self-care phase to standard Vibroacoustic treatment could be beneficial for maintaining the effects from the more intensive Vibroacoustic treatment as part of multidisciplinary rehabilitation. Implications for rehabilitation Chronic pain and comorbid mood disorders negatively impact functioning and ability to work. Vibroacoustic treatment with a self-care phase could be beneficial for managing the symptoms of chronic pain if implemented within a naturalistic multidisciplinary rehabilitation context. In four single cases, this study shows functioning, pain, and depression improved after Vibroacoustic treatment with self-care.